Evaluation of the SCARF Well‐Being and Suicide Prevention Program for Rural Australian Communities. Issue 2 (6th May 2019) - Perceval, Meg; Reddy, Prasuna; Ross, Victoria; Joiner, Thomas; Kolves, Kairi
Abstract: Purpose: Rural communities in Australia have an elevated risk of suicide. The aim of the current study was to evaluate a well‐being and suicide prevention education workshop, SCARF (Suspect, Connect, Ask, Refer, Follow‐Up) developed for Australian farming and rural communities. Methods: The SCARF program was delivered to 14 groups, a convenience sample including frontline agricultural workers and farmers from New South Wales. The Literacy of Suicide Scale, Stigma of Suicide Scale, and items assessing confidence to assist others were administered immediately before and after the workshop, and at 3‐month follow‐up. The Warwick Edinburgh Mental Wellbeing Scale was given immediately before and at 3‐month follow‐up. In total, 255 agreed to participate in the study, with 127 completing 3‐month follow‐up. Data were analyzed using linear mixed‐effects regression. Findings: There was a significant increase in suicide literacy and confidence to assist others immediately after the workshop, which remained significant at 3‐month follow‐up. Mental well‐being significantly improved at 3‐month follow‐up. Conclusion: The SCARF program is unique for its brevity, cultural specificity, focus on health, and incorporation of the biopsycho‐ecological model and the Interpersonal Theory of Suicide. It represents a useful program for Australian farming and rural communities to improve mental well‐being, suicide literacy, and confidence to recognize and respond to suicidality.